2019
DOI: 10.1039/c9ra05222d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the endoplasmic reticulum localization sequence and N-glycosylation of matrix metalloproteinase 26

Abstract: Matrix metalloproteinase 26 (MMP-26), also called endometase and matrilysin-2, belongs to the MMP superfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…MMPs are generally excreted via the endoplasmic reticulum as a result of the N-terminal secretory signal [ 1 , 21 ]. However, in HEK293 cells, about half of nascent MMP-2 is retained inside the cell due to an inefficient secretory signal sequence [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are generally excreted via the endoplasmic reticulum as a result of the N-terminal secretory signal [ 1 , 21 ]. However, in HEK293 cells, about half of nascent MMP-2 is retained inside the cell due to an inefficient secretory signal sequence [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the misfolded protein produced by a truncated set of genes will be retained in the ER and processed for ER-related degradation [ 51 ], the deletion of rfa genes may lead to the further interference of the membrane’s subsequent function [ 50 ]. Moreover, glycosylation deficiencies in the LPS protein production also disrupt protein localization in ER, which affects the functional membrane of protein [ 52 ]. In addition, the KEGG prediction showed high expression of PFKA, GAPA, and PYKA in E. coli by rfaL gene knockout ( Figure 7 b).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, misfolded proteins are retained in the ER and processed for ER-associated degradation ( Araki and Nagata, 2012 ). Glycosylation deficiencies can disrupt protein localization in the ER ( Zhang et al, 2019 ). In this study, we identified three N-glycosylation sites in the full-length PDGF-C protein that include Asn25, Asn55, and Asn254.…”
Section: Discussionmentioning
confidence: 99%